PENGARUH PENGALAMAN MENGAJAR DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMK LABOR BINAAN FKIP UNIVERSITAS RIAU PEKANBARU - Putri, Rahmi; ', Sumarno; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: Teaching experience is a task to be done by teachers with supporting factors and increase knowledge in the work. Labor discipline is an attitude of respect, honor, obey and comply with applicable regulations without violating the rules that have been defined. Teacher performance is the result of work that has been accomplished by a teacher as an educator to achieve educational goals. This study aims to determine the effect of teaching and discipline of work on teacher performance. The population in this study are all teachers of SMK Labor Binaan FKIP UNRI, using sampling techniques through sampling methods saturated. Data were collected using questionnaires and documentation. Data were analyzed using multiple linear regression analysis, t test and F test with significance level of 0.05%. Based on the research showed that the experience of teaching and discipline simultaneously positive and significant impact on teacher performance. It is based on the analysis results, which show the calculation results F test > F table (11.656 > 3.316). Furthermore, by t test to determine whether each of the independent variables affect the dependent variable. The results showed a partial teaching experience no significant effect on the performance of teachers. This is evidenced in which t test < t table (1.691 < 2.042). Further to the work discipline variable indicates that a significant effect on the performance of teachers. This is evidenced in which thitung> t table (4.620> 2.042). The predictive ability of the two variables on the performance of teachers in the study amounted to 43.7% (R Square .437) while the remaining 56.3% is influenced by other factors which are not included in this study.Keywords: teaching experience, work discipline, teacher performance.